Islamic Criticism (Kant & Faruqi's Synthesis): A New Paradigm for Understanding the World in a Whole and Integrated Manner - Mohamad Topan; Rr. S. Murtiningsih; A. H. Utomo (TSAQAFAH, 2026)
Modernity faces a crisis of meaning marked by the fragmentation of knowledge and the separation of facts from values. This article responds to this by presenting a visionary synthesis between Immanuel Kant's critical epistemology from the Western tradition and Ismail Raji Al-Faruqi's project of Islamizing knowledge. Kant, with his distinction between phenomena-noumena, reminds us of the limits of human reason, which can only reach the empirical world. Meanwhile, Al-Faruqi offers the Tawhid paradigm as an integrative principle that combines revelation, reason, and sensory experience. Through a comparative-hermeneutical analysis, this research develops the framework of "Islamic Criticism"—a paradigm that maintains Kantian critical and a priori attitudes, but transcends the dualism of phenomena and noumena by asserting that transcendent reality can be accessed through revelation, natural instinct, and spiritual experience (ma'rifah). In this hierarchical synthesis, revelation serves as a normative guide for reason and empiricism. Its implications offer epistemological reintegration, a holistic educational model (insan kamil), a transcendent global ethical foundation, and a path for equal dialogue between civilizations. This synthesis is a foundational answer to the problem of disenchantment in modernity.